Analisis Pengembangan Kompetensi Pendidik dan Tenaga Kependidikan dalam Mewujudkan Generasi Islami - Nailan, Akhmaliah Siti; Sulastri, Asri; Supendi, Pepen (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2023)
This study aims to analyze the development of the competence of educators and education personnel in MI Manba’ul Huda based on national standard of educator and education personel in accordance with Permendiknas. The object of this research is the entire educators and education personel in MI Manba’ul Huda. Then the research approach used is a descriptive qualitative research approach with research instruments including observation, interviews, and documentation. Based on the results of the analysis obtained that the standar and competence of educators and education personel in MI Manba’ul Huda have a fairly good value with a percentage of 77% or a value of 58 from maximum value of 76. There are four indicators that have a value below 3 or B, namely regarding madrasah special personnel, competence and certification of library staff, the ratio of conseling teacher and the competence of counseling teachers. The strategy carried out in improving the competence of educators and education personnel by including teacher in training in accordance with the field of ability they are capable of to produce competent educators and continue to apply Islamic values.